PENGAMATAN KESTABILAN LERENG TAMBANG MENGGUNAKAN SLOPE STABILITY RADAR (SSR) - -, Supandi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
Maintenance of the mine slope stability is very important to maintain continuity of mining activities. Although the mine design is done by carefully using several methods and approaches, but often there is a failure due to design limitations of geological information. In this case it is necessary to minimize the effects of a monitoring tool that can detect early indications of instability. In this study aims to determine the function of Slope Stability Radar (SSR) in the monitoring of slope stability is the end goal is to avoid negative impacts and risks of failure can be avoided mine design and sustainability of mining activities can proceed safely. In this study the observations using the Slope Stability Radar (SSR). Radars placed at a point perpendicular to the object in the observed and the radar will emit a wave toward the object and the object wave will be sent back and will be captured by the radar..In this study, the radar is installed in a certain position to monitor the movement of the walls of the mine and the results of research can be in the relationship between the movement of the actual conditions that exist. Monitoring the stability of the wall using the radar continues to be done at the time of stabilization and stabilization has been finished when done. Monitoring was stopped when the mine wall stabilisasi and activity near the ravine has been finished and there is no indication of movement of the slope. From this research produced the conclusion that the use of slope stability radar (SSR) are very helpful and effective for the observation of slope stability, especially to minimize the risk of mining activities.